EXAMINING THE BUILT FORM IN SEREMBAN TOWN FOR TOWN-PLAN ANALYSIS - Yaktor Joshua Inusa; Doris Hooi Chyee Toe; Kum Weng Yong (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper examined the built form in Seremban town at the urban tissue scale to establish a basis for town-plan analysis of its historic urban core. A buffer was created around each location centre of 25 areas within the boundary of Seremban town (Bandar Seremban), defining an area considered to cover a walking distance of 500m radius; the urban tissues of 13 areas were selected for analysis. The location centres were identified based on geospatial data from the Department of Survey and Mapping Malaysia obtained in November 2020. Two distinct morphological characters exist in the current town plan of Seremban – the grid-iron (regular) and organic (irregular) patterns. The grid-iron pattern is predominantly visible in the historic urban core while the organic pattern dominates on the periphery. Also, areas identified within the boundary are sparsely distributed in the northern part while in the southern area, they are densely clustered. Therefore, the highest number of overlaps in the northern area is three, whereas up to six are identified in the southern area. This paper is a unique analysis of the built form with two distinct morphological characters. It is important in town-plan analysis of the urban form in Seremban as the study is context specific.